2022
DOI: 10.1186/s12885-022-09286-w
|View full text |Cite
|
Sign up to set email alerts
|

ZNF703 promotes triple-negative breast cancer cells through cell-cycle signaling and associated with poor prognosis

Abstract: Background The oncogenic drivers of triple-negative breast cancer (TNBC), which is characterized by worst prognosis compared with other subtypes, are poorly understood. Although next-generation sequencing technology has facilitated identifying potential targets, few of the findings have been translated into daily clinical practice. The present study is aimed to explore ZNF703 (Zinc finger 703) function and its underlying mechanism in TNBC. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…At present, in accordance with the different number of conserved Cys and His residues bound to Zn 2+ , zinc nger structure can be divided into C2H2, C2HC, C3H, C4, C3HC4, C4HC3, C6, C8 and other types, among which C2H2 is the largest one [31] . With the updating of cancer databases and the development of bioinformatics, many C2H2 zinc nger proteins such as ZNF217 [32] , ZNF703 [33] , ZNF32 [34] have been excavated, and their functions and mechanisms in different cancers have been gradually revealed. These basic studies have important scienti c signi cance and value for the future clinical precision treatment of BC.…”
Section: Discussionmentioning
confidence: 99%
“…At present, in accordance with the different number of conserved Cys and His residues bound to Zn 2+ , zinc nger structure can be divided into C2H2, C2HC, C3H, C4, C3HC4, C4HC3, C6, C8 and other types, among which C2H2 is the largest one [31] . With the updating of cancer databases and the development of bioinformatics, many C2H2 zinc nger proteins such as ZNF217 [32] , ZNF703 [33] , ZNF32 [34] have been excavated, and their functions and mechanisms in different cancers have been gradually revealed. These basic studies have important scienti c signi cance and value for the future clinical precision treatment of BC.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical observation study ( 69 ) via the cross-sectional method indicated that AGR2 expression is positively associated with the incidence of distant metastases in BRCA and upregulated AGR2 was a poor prognosis predictor. Current research reported that ZNF703 expressed in approximately 34.2% of TNBC via immunohistochemistry and the knockdown of ZNF703 triggered a powerful inhibition of TNBC cell proliferation and cell cycle, along with the downregulation of cyclin D1, CDK4, CDK6, and E2F1 ( 70 ). Remaining genes were firstly explored to have effects on the prognosis of TNBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-30c has also recently been considered as a suppressor of bone gamma-carboxyglutamate protein ( BGLAP ) in osteogenesis ( 50 ). Target DEGs of miR-30c in our analysis were mostly related to the anti-apoptosis of abnormal tumor cells, including MAP3K9 in lung cancer ( 46 ), ST6GALNAC5 in prostate cancer ( 51 ), CSRNP3 in clear renal cell carcinoma ( 52 ), ZNF703 in breast tumors ( 53 ), and CLSPN in brain tumors ( 54 ). Thus, upregulation of hsa_circ_0102564 might help reveal the downstream mechanism involved in the abnormal maturation and proliferation of chondrocytes in OA.…”
Section: Discussionmentioning
confidence: 93%